Reversal of Endothelial Extracellular Vesicle-Induced Smooth Muscle Phenotype Transition by Hypercholesterolemia Stimulation: Role of NLRP3 Inflammasome Activation - Yuan, Xinxu; Bhat, Owais M.; Samidurai, Arun; Das, Anindita; Zhang, Yang; Li, Pin-Lan (Frontiers in Cell and Developmental Biology, 2020)
Recent studies reported that vascular endothelial cells (ECs) secrete NLR family pyrin domain-containing 3 (NLRP3) inflammasome products such as interleukin-1β (IL-1β) via extracellular vesicles (EVs) under various pathological conditions. EVs represent one of the critical mechanisms mediating the cell-to-cell communication between ECs and vascular smooth muscle cells (VSMCs). However, whether or not the inflammasome-dependent EVs directly participate in the regulation of VSMC function remains unknown. In the present study, we found that in cultured carotid ECs, atherogenic stimulation by oxysterol 7-ketocholesterol (7-Ket) induced NLRP3 inflammasome formation and activation, reduced lysosome-multivesicular bodies (MVBs) fusion, and increased secretion of EVs that contain inflammasome product IL-1β. These EC-derived IL-1β-containing EVs promoted synthetic phenotype transition of co-cultured VSMCs, whereas EVs from unstimulated ECs have the opposite effects. Moreover, acid ceramidase (AC) deficiency or lysosome inhibition further exaggerated the 7-Ket-induced release of IL-1β-containing EVs in ECs. Using a Western diet (WD)-induced hypercholesterolemia mouse model, we found that endothelial-specific AC gene knockout mice (Asah1fl/fl/ECCre) exhibited augmented WD-induced EV secretion with IL-1β and more significantly decreased the interaction of MVBs with lysosomes in the carotid arterial wall compared to their wild-type littermates (WT/WT). The endothelial AC deficiency in Asah1fl/fl/ECCre mice also resulted in enhanced VSMC phenotype transition and accelerated neointima formation. Together, these results suggest that NLRP3 inflammasome-dependent IL-1β production during hypercholesterolemia promotes VSMC phenotype transition to synthetic status via EV machinery, which is controlled by lysosomal AC activity. Our findings provide novel mechanistic insights into understanding the pathogenic role of endothelial NLRP3 inflammasome in vascular injury through EV-mediated EC-to-VSMC regulation.